Global Analysis of Cell Wall Genes Revealed Putative Virulence Factors in the Dermatophyte Trichophyton rubrum - Martins, Maíra P.; Silva, Larissa G.; Rossi, Antonio; Sanches, Pablo R.; Souza, Larissa D. R.; Martinez-Rossi, Nilce M. (Frontiers in Microbiology, 2019)
The fungal cell wall is a structure in constant contact with the external environment. It confers shape to the cell and protects it from external threats. During host adaptation, the cell wall structure of fungal pathogens is continuously reshaped by the orchestrated action of numerous genes. These genes respond to environmental stresses and challenging growth conditions, influencing the infective potential of the fungus. Here, we aimed to identify cell wall biosynthesis-related genes that putatively encode virulence factors in Trichophyton rubrum. We used RNA-seq to examine the impact of two drugs, namely undecanoic acid, and acriflavine as well as the effects of the carbon source switching from glucose to keratin on T. rubrum cell wall metabolism. By using functional annotation based on GO terms, we identified significantly differentially expressed cell wall-related genes in all stress conditions. We also exposed T. rubrum to osmotic and other cell wall stressors and evaluated the susceptibility and gene modulation in response to stress. The changes in the ambient environment caused continuous cell wall remodeling, forcing the fungus to undergo modulatory restructuring. The influence of the external challenges indicated a highly complex response pattern. The genes that were modulated simultaneously in the three stress conditions highlight potential targets for antifungal development.